“What Would You Do About It?” : Mother and Daughter Bedtime Conversation on Daughter’s Preference - Winarti, Oktifani (LPPM Stikosa - AWS, 2024)
This study explores the dynamic interactions between mothers and daughters during bedtime conversations, focusing on how these exchanges contribute to emotional and behavioral development in children. By analyzing naturally occurring dialogues captured through social media, the research illustrates the pivotal role of bedtime storytelling and dialogue in fostering secure attachments and aiding in stress management and emotional regulation in young children. The conversations, characterized by responsive speech and turn-taking, not only strengthen familial bonds but also serve as a critical educational tool, enabling children to navigate complex emotional landscapes and articulate their needs effectively. These interactions are shown to be instrumental in promoting positive behavioral outcomes and enhancing a child's ability to handle stress, thus laying a foundational framework for healthy emotional development. The findings suggest that intentional, nurturing communication at bedtime can have profound long-term benefits for child development, advocating for its integration into daily parenting practices.